Development of an Active Deep Learning Experience-Based Group Guidance Module with Islamic Values to Increase the Academic Self-Efficacy of High School Students - Riski Putra Ayu Distira; Moh. Yusuf Efendi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This research aims to develop and validate an innovative group guidance module that integrates Active Deep Learning Experience with Islamic values to enhance the academic self-efficacy of high school students. Using the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study involved 10–15 students in the limited trial and 30–40 students in the field trial, selected through purposive sampling based on low self-efficacy levels. Data were collected through interviews, questionnaires, observations, and documentation, and analyzed qualitatively using an interactive model and quantitatively through a paired sample t-test to compare pretest and posttest results. The findings indicated a significant improvement in students’ academic self-efficacy (t = 6.27; p < 0.05) from the medium to high category, supported by positive student responses where over 90% found the module useful, easy to apply, and relevant to their academic needs. This research contributes to the integration of Bandura’s self-efficacy theory and Active Deep Learning principles within an Islamic educational framework, offering a new paradigm in counseling that bridges psychological growth and spiritual values.